KEMAMPUAN MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMK NEGERI 1 LHOKSUKON, KABUPATEN ACEH UTARA - Teuku Miftahuddin; Khairuddin .; Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2014)
Abstract: Managerial competence of principal can improve the performance of teachers in order to improve the quality of education. The purpose of this study was to determine the program planning, implementation and follow-up of managerial competence of principal in State Vocational High School 1 of Lhoksukon in Aceh Utara Regency. This study used a qualitative approach and descriptive method. Data collection techniques used were observation, interview and documentation study. The subjects of this study were principal, vice principal, teachers, school committee and school treasurer. The results of this study showed that: (1) Program planning of managerial competence of the principal was developing programs to improve teacher performance. (2) The program was implemented by improving teacher performance through provision of awards, opportunities, challenges, empowerment and high responsibility development. (3) The follow-up of the program was the establishment of open and democratic communication between the principal and the school personnel.Keywords: Managerial competence of Principal and Teacher PerformanceAbstrak: Kemampuan manajerial kepala sekolah dapat meningkatkan kinerja guru untuk peningkatan mutu pendidikan. Tujuan penelitian ini adalah untuk mengetahui program perencanaan, pelaksanaan dan tindak lanjut kemampuan manajerial Kepala SMK Negeri 1 Lhoksukon Kabupaten Aceh Utara. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif, teknik pengumpulan data dengan observasi, wawancara dan studi dokumentasi subjek penelitian ini kepala sekolah, wakil kepala sekolah, guru, komite sekolah dan bendahara. Penelitian ini memberi kesimpulan: (1) Program perencanaan kemampuan manajerial Kepala SMK Negeri 1 Lhoksukon Kabupaten Aceh Utara adalah mengembangkan program-program peningkatan kinerja guru. (2) Pelaksanaannya adalah menerapkan program peningkatan kinerja guru melalui pemberian penghargaan, kesempatan, tantangan, pemberdayaan dan pengembangan tanggungjawab yang tinggi. (3) Tindak lanjutnya adalah membentuk komunikasi personil sekolah dengan kepala sekolah dilaksanakan secara terbuka dan demokratis.Kata kunci : Kemampuan Manajerial Kepala Sekolah dan Kinerja Guru